Linear relationships between leaf incidence and severity in multiple pathossystem of leaf spots in irrigated rice Relações lineares entre incidência e severidade foliar em patossistema multiplo de manchas foliares em arroz irrigado - Bordin L.C. (2016)
© 2016, Universidade Estadual Paulista (UNESP). All rights reserved.The occurrence of leaf diseases in irrigated rice can reduce yield and grain quality. The aim of this study was to evaluate the relationship between incidence and severity in the intensity of leaf spots in irrigated rice. Experiments were conducted with the rice cultivar SCS 116 Satoru in 2011/12 and 2012/13 growing seasons in Rio do Oeste, located in Alto Vale do Itajaí, Santa Catarina State, Brazil. The design was in randomized blocks with four replicates and six treatments consisting of applications of a mixture of the fungicides triazole (difenoconazole) and strobilurin (azoxystrobin), which included one application at the end of tillering (V8), two applications (V8 + R0, panicle initiation), three applications (V8 + R0 + R2, booting), four applications (V8 + R0 + R2 + R4, flowering), five applications (V8 + R0 + R2 + R4 + R6, milky grain), with the objective to create a disease intensity gradient. Before each application, the incidence and the severity of leaf diseases were determined. In both growing seasons, the predominant leaf diseases were blast, brown spot and scald. The obtained data were subjected to regression analysis. Using the equation that best fit in both crop seasons and substituting the severity value for 1%, the incidences of 30.80; 35.86; 25.91; 30.26; 32.90 were obtained at the phenological stages of tillering, panicle initiation, booting, flowering and milky grain, respectively. The disease severity estimated based on the incidence and vice-versa allows its use for technical assistance in the monitoring of leaf spots in irrigated rice.